Stosunek studentów do stosowania kar cielesnych wobec dzieci - Joanna Frankowiak (Problemy Wczesnej Edukacji)
The article presents the results of research on social attitudes of university students against violence. Specifically, their reference to claims that corporal punishment is applied to children. The research results indicate a higher approval of men. The place of origin is not a differentiating indication. Only 43% of respondents know about the legal prohibition of corporal punishment. The final part reflects on preventive measures that could be addressed to students.